Size, Age, and Spatial-Temporal Distribution of Shortfin Mako in the Mexican Pacific Ocean - Carreón Zapiain, María Teresa; Favela Lara, Susana; González Pérez, Jaime Otilio; Tavares, R.; Leija Tristán, Antonio; Mercado Hernández, Roberto; Compeán Jiménez, G. A. (2018)
Abstract Basic population parameters such as age, size, and distribution have been poorly evaluated for the Shortﬁn Mako Isurus oxyrinchus in the Mexican Paciﬁc Ocean. According to data collected by scientiﬁc observers on board medium-size ﬁshing vessels during the period of 2006–2013, size as TL was obtained for 5,740 individual sharks. The range of TL was 70–362 cm for females and 71–296 cm for males. Weight (W), measured randomly from 1,409 individuals, ranged from 2 to 90 kg for females and from 2 to 80 kg for males. The weight-to-TL ratio was best ﬁtted by the equation W = 4 × 10−5(TL)2.59 (r2 = 0.6532). No sex-speciﬁc difference was found in the weight-to-TL relationship between males and females, nor in W or TL separately. By using the inverse von Bertalanffy equation and parameters described by other authors for the same study area, we determined the age range for individuals captured on the basis of their TL. The age ranged from 0 to 39 years in females and from 0 to 21 years in males. Using a logistic model, the mean length at sexual maturity was obtained for 2,532 males (TL = 190 cm). The quarterly distribution of young of the year and 1-year-old juveniles showed that there is a tendency for these sharks to move